Impact of emergency hospital admissions on patterns of primary care prescribing: a retrospective cohort analysis of electronic records in England - Denholm, Rachel (Br J Gen Pract, 2020)
BACKGROUND: Little is known about the impact of hospitalisation on prescribing in UK clinical practice. AIM: To investigate whether an emergency hospital admission drives increases in polypharmacy and potentially inappropriate prescriptions (PIPs). DESIGN AND SETTING: A retrospective cohort analysis set in primary and secondary care in England. METHOD: Changes in number of prescriptions and PIPs following an emergency hospital admission in 2014 (at admission and 4 weeks post-discharge), and 6 months post-discharge were calculated among 37 761 adult patients. Regression models were used to investigate changes in prescribing following an admission. RESULTS: Emergency attendees surviving 6 months (N = 32 657) had a mean of 4.4 (standard deviation [SD] = 4.6) prescriptions before admission, and a mean of 4.7 (SD = 4.7; P<0.001) 4 weeks after discharge. Small increases (<0.5) in the number of prescriptions at 4 weeks were observed across most hospital specialties, except for surgery (−0.02; SD = 0.65) and cardiology (2.1; SD = 2.6). The amount of PIPs increased after hospitalisation; 4.0% of patients had ≥1 PIP immediately before pre-admission, increasing to 8.0% 4 weeks post-discharge. Across hospital specialties, increases in the proportion of patients with a PIP ranged from 2.1% in obstetrics and gynaecology to 8.0% in cardiology. Patients were, on average, prescribed fewer medicines at 6 months compared with 4 weeks post-discharge (mean = 4.1; SD = 4.6; P<0.001). PIPs decreased to 5.4% (n = 1751) of patients. CONCLUSION: Perceptions that hospitalisation is a consistent factor driving rises in polypharmacy are unfounded. Increases in prescribing post-hospitalisation reflect appropriate clinical response to acute illness, whereas decreases are more likely in patients who are multimorbid, reflecting a focus on deprescribing and medicines optimisation in these individuals. Increases in PIPs remain a concern.